REGIONAL LINGUISTIC CONSCIOUSNESS: CORE AND PERIPHERY - Ilyichova, Inna (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The article examines the issues of modeling a fragment of the linguistic consciousness of residents of the Brest region. The study aims to identify and describe the stereotypicality and variability in the semantic content of the images of perception of the Brest region by representatives of the regional society. As a research method, a freeassociative experiment is used within the framework of the implementation of the joint research project «Brest Region through the Eyes of People of Different Professions». The methodology includes quantitative and qualitative analysis of the entire set of associative reactions obtained, identification of associative fields for each target group, and formation of an integrated structure (associative macro field «Brest Region»). Comparative analysis of the core zone of representatives of different spheres of activity allows identifying semantic intersections between the elements of the cores. The semantic analysis shows the distribution of the obtained core reactions into several thematic groups. Linguistic analysis of the peripheral zone, taking into account structural features, indicates the presence of four main types (reactions-words, reactions-phrases, reactions-sentences, reactions-texts). The practical significance of the study lies in the possibility of using the results of the study to develop communication strategies in the process of forming the image policy of the Brest region.
Keywords: linguistic consciousness; the core of the associative field; associative reactions; peripheral associative reactions; thematic groups; core density index; stereotypical reactions; variable reactions